Internalisasi nilai-nilai Al-qur’an dalam kehidupan sosial masyarakat muslim Indonesia - JABIR, MUHAMMAD (Maliki Interdisciplinary Journal, 2026)
The Qur’an guides humans in social interaction. Digital incivility such as hate speech reflects moral degradation that must be reoriented through Qur’anic ethics. Meanwhile, the Barikan tradition as a form of Living Qur’an in Javanese society strengthens Islamic brotherhood, social care, gratitude, and harmony. This study aims to analyze the concept of al-insan in the Qur’an and the implementation of Qur’anic values in Indonesia’s social life through communication ethics and the Barikan cultural tradition. This research uses library studies and thematic analysis of Qur’anic verses and previous research. The results show that humans possess good and bad potentials; therefore, internalizing Qur’anic values is essential to promote polite communication and build social harmony.The implications of this research indicate that implementing Quranic-based communication ethics is crucial in facing the challenges of the digital era, particularly in minimizing hate speech and increasing public moral awareness. Furthermore, strengthening local traditions such as Barikan can be an effective medium for grounding Quranic values ​​in a contextual and applicable manner. Therefore, the synergy between understanding the sacred text and local cultural practices needs to be continuously developed in an effort to shape a moral, tolerant, and civilized society amidst the currents of globalization.